The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1073/pnas.1525745113
|View full text |Cite
|
Sign up to set email alerts
|

Global informatics and physical property selection in protein sequences

Abstract: The degree of informatic independence between the physical properties of amino acids as encoded in actual protein sequences is calculated. It is shown that no physical property can be identified that carries significantly less information than others and that the information overlap between different properties and different length scales along the sequence is essentially zero. These observations suggest that bioinformatic models based on arbitrarily selected sets of physical properties are inherently deficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(20 citation statements)
references
References 13 publications
0
19
1
Order By: Relevance
“…The behavior summarized in Figure is qualitatively different from that observed when the 10 static property factors were compared in the same way . In that case, we found that all the significant sequence differences between architectural groups, at every level of the hierarchy, fall in the first bin (0 ≤ k ≤ 10).…”
Section: Resultscontrasting
confidence: 60%
See 2 more Smart Citations
“…The behavior summarized in Figure is qualitatively different from that observed when the 10 static property factors were compared in the same way . In that case, we found that all the significant sequence differences between architectural groups, at every level of the hierarchy, fall in the first bin (0 ≤ k ≤ 10).…”
Section: Resultscontrasting
confidence: 60%
“…If this is the case, we expect that groups of proteins that fold to different architectures will exhibit statistically significant differences in their dynamic propensities. We ask whether this is so, by addressing two specific questions: Are there indeed statistically significant differences in the characteristics of dynamic sequences between groups of proteins known to fold to different architectures? Is the behavior of those characteristics different from that we have observed for static properties? …”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…This representation carries 86% of the variance of the entire set of available physical properties (45,46). We have further shown (48) that the representation cannot be simplified, because any deviation from the full property factor representation results in a loss of physical information. No factor encodes information about any of the others, and all encode roughly equal amounts.…”
Section: Discussionmentioning
confidence: 96%
“…In this context, ProtDCal is a software package that transforms protein sequences or 3D‐structures into general‐purpose numerical descriptors, accounting for both global and local information . Due to its complementary performance with respect to other well‐established tools in the field like PROFEAT and PseAcc (later extended to Pse‐in‐one), ProtDCal has been used in a number of studies . Notable among them are the modeling of posttranslational modifications, the prediction of protein enzymatic function, the prediction of antimicrobial activity in peptides, the determination of residues critical for protein function, and the prediction of stability changes upon mutations .…”
Section: Introductionmentioning
confidence: 99%